Impedance Spectroscopy Analysis of a Liquid Tin Anode Fuel Cell in Voltage Recovery Mode - Prattana Kaewpet; Klaus Hellgardt (My University, 2016)
A concept of a liquid tin anode-indirect carbon air fuel cell (LTA-ICFC) are described.Experimental setups for analysis of LTA-ICFC polarisations of an operational electrochemical reactor of the LTA-ICFC are presented.Results from Electrochemical Impedance Spectroscopy (EIS) Analysis of the electrochemical reactor of the LTA-ICFC are shown and analysed.The rate-determining step of the system is concluded.The charge-transfer resistance did not show considerable differences at 700-800 °C.This can be implied that the charge-transfer resistance is not the rate-limiting step of the transport processes of the fuel cell.The increase of the Warburg impedance concurrently with the resistance to fit mass-transport loss (R3) suggests that the rate-limiting step for the LTA-ICFC in voltage recovery mode is the diffusion of the oxide ions through SnO 2 layer.The increment of mass transport lost, R3, of the cell causes the slowly increase of the cell's voltage over the voltage from 0.7-0.8V at 700, 750, and 800 °C.
Keywords: Fuel Cells and Related Materials